The Return to Hours Worked within and across Occupations: Implications for the Gender Wage Gap - Jeffrey T. Denning; Brian A. Jacob; Lars Lefgren; Christian vom Lehn (Institute of Labor Economics (IZA), 2021)
Prior research suggests that gender differences in hours worked play an important role in the gender pay gap. Yet common estimates of the wage returns to hours worked are close to zero, implying that hours differences cannot account much for the gender wage gap, even though men work more hours than women on average. However, while the wage returns to hours worked within occupation are small, we document that the wage returns to average hours worked across occupations are large. We develop a conceptual framework that reconciles these facts. We show that, under some assumptions, gender differences in hours worked can account for a substantial portion of the gender wage gap and that increases in the returns to hours worked over the past four decades slowed progress in reducing the gender pay gap.
Keywords: J16; J22; J31; J33; 330; hours; wages; occupation; gender wage gap